2016
DOI: 10.15386/cjmed-579
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Gla protein in tumoral pathology

Abstract: Matrix Gla protein is a vitamin K-dependent protein secreted by chondrocytes and vascular smooth muscle cells. The presence of matrix Gla protein was reported in arterial and venous walls, lungs, kidney, uterus, heart, tooth cementum and eyes. Several studies identified matrix Gla protein in tumoral pathology.Until recently, it was thought to only have an inhibitory role of physiological and ectopic calcification. New studies demonstrated that it also has a role in physiological and pathological angiogenesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 25 publications
0
23
0
2
Order By: Relevance
“…Among the 17 Gla-protein members, Periostin (POSTN) and Matrix Gla-Protein (MGP) are known to affect ECM crosslinking and various cellular behaviors, such as migration, adhesion and proliferation in epithelial, endothelial, fibroblast, osteoblast and myocyte cells (23)(24)(25)(26)(27). POSTN is expressed in osteoblast, mesangial, fibroblast, mesenchymal and vascular smooth muscle cells (22), while MGP is typically secreted and localized in the surrounding ECM of chondrocytes or endothelial cells (28).…”
Section: Introductionmentioning
confidence: 99%
“…Among the 17 Gla-protein members, Periostin (POSTN) and Matrix Gla-Protein (MGP) are known to affect ECM crosslinking and various cellular behaviors, such as migration, adhesion and proliferation in epithelial, endothelial, fibroblast, osteoblast and myocyte cells (23)(24)(25)(26)(27). POSTN is expressed in osteoblast, mesangial, fibroblast, mesenchymal and vascular smooth muscle cells (22), while MGP is typically secreted and localized in the surrounding ECM of chondrocytes or endothelial cells (28).…”
Section: Introductionmentioning
confidence: 99%
“…Further investigation demonstrated that MGP had a wider range of activities, which were dependent of the phosphorylation-carboxylation status, protein expression and variants. Recent studies showed that MGP has a role in tumor angiogenesis by increasing vascular endothelial growth factor gene expression [51][52][53]. Recently, MGP was reported to be upregulated in a variety of tumors, including ovarian, breast, urogenital and skin cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that the discrepancy between the tissue regions analyzed by DNA microarray and those subjected to immunohistochemical analysis led to this result. The relatively low immunoreactivity scores of GPNMB and MGP may be attributed to the timing of degradation and wash-out of these proteins from the tissue [53].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed aberrant expression of MGP in various types of cancers and exert dual biological functions, acting as an oncogene or tumor‐suppressor, by regulating the expression of different target genes (Gheorghe and Crăciun, 2016). However, the regulatory role of MGP in tumorigenesis is still controversial.…”
Section: Introductionmentioning
confidence: 99%